Minister Mohammed bin Abdul-Malik al-Zayat (D. 233 AH ( Historical Study - تركي عليوي خالد; محمد احمد عمر (Al-Adab Journal, 2018)
Appearing at al abassi age alof of good ministers who has abig onle in running of state matters , from there was the minister monhamed bin abd almalik alzayat who appoint as minister to three from bani albas califah there was al Muatasim , al Wathiq , and al Mutawakil . al Muatasim califah appoint him minister in 220H , and he depend on him in big way , and he lift from himself when he know his ability and wisdam in running of state matters , in addition to what was he his from culture and letters , he was poet and polite , and he his collection of poems and collection of letters , and he cauntinue in his position until . Al mu’atasim death , then al wathiq appoint him minister and he lift from himself more than Al mu’atasim reign , and coining his name on al drahim and al dananeer , and he stay in position until alwathiq , then al mutawakil appoint him aminister little time and disaste him and kill him in 233H in fnrnace